Processo de trabalho das equipes de saúde bucal na atenção básica do Brasil - Fagundes, Daniela Malagoni (2016)
Introduction: The Program for Improving Access and Quality of Primary Care (PIAQ-PC) was implemented in Brazil in 2011 to induce improvements in the quality of services and management in Primary Care (PC) in Health System (HS). However, there are only scarce studies evaluating the work process of the Oral Health Teams (OHT) in PC of HS using PIAQ-PC data. Besides, bearing in mind that the current health care model in this area is not ideal, it is appropriate to conduct this study. Objective: To analyze the work process developed by OHT of PC and to verify if the instrument used in Cycle I of the PIAQ-PC was able to measure the essential attributes of Primary Health Care (PHC). Method: A nationwide ecological study was developed where the analytical units were aggregated to the level of the municipality, using PIAQ-PC data regarding the interviews with professionals from OHT (module II). It has been conducted exploratory and confirmatory factor analysis to test whether the variables of PIAQ-PC’ s Cycle I external evaluation instrument, which refers to the work process of the OHT, could be reduced to the essential attributes of the PHC (first contact, completeness, longitudinality and coordination of care), adopting alpha of 5%. We also carried out a descriptive analysis to analyze the work process of these teams in Brazil. All variables included in the model after the factor analysis were summarized by absolute and percentage frequencies, and the Chi-Square (X2) and Fisher Exact tests were used to analyze the differences in their distribution according to the political region, type of staff and PIAQ-AC certification stratum (α=1%). Results: It was formed four constructs, which we call first contact (factor 1), completeness (factor 2), actions in dental prosthesis (factor 3) and coordination of care (factor 4). The model adjustment measures were satisfactory. The factorial loadings (FL) of all first-order constructs were greater than 0.5, except for the “coordination of care”, which had two variables with FL < 0.5, however, significant. A second-order construct (formed by the four factors to define the work process) had all FL > 0.7, but with adjustment rate not so robust (Comparative Fit Index and Tucker Lewis Index less than 0.9). Actions and oral health services related to the essential attributes of PHC were performed for less than half of Brazilian OHT, except “home to spontaneous demand” (61.8%), “risk assessment” (66.1%), “treatment provision according to identified risk” (60.2%) and “ensuring continuity of care” (62.3%). The worst results were for actions related to factors 2 and 3. There were differences in the performance of actions between regions, type of staff and socioeconomic level of the municipalities (P < 0.01). Conclusions: The instrument of PIAQ-PC first cycle was not able to determine all the essential attributes of PHC in the service routine. The OHC of PC in Brazil are not working according to the essential attributes of PHC, and there are still many discrepancies in the work process.